Inspection of crude oil condition using electronic nose (E-nose) - Nur Ain Zarani, Zailani; Muhammad Sharfi, Najib; Suhaimi, Mohd Daud; Mujahid, Mohamad; Saiful Nizam, Tajuddin; Che Mohd Aizal, Che Mohd (Penerbit UMP, 2020)
Oil and gas production and distribution processes technologies are highly complex and capital-intensive. Crude oil is a high demand commodity in Malaysia and across the world. Physical and chemical properties are used to classify crude oil in oil and gas industries. The human's nose cannot distinguish the difference of smell among various crude oils grade. Conventional approaches to detect odour are expensive and difficult to operate. Due to declining production and increasing demand, using E-nose technologies to inspect the odour condition of crude oil might be a significant change in the industries. The Case-Based Reasoning (CBR) classification method also is utilised in this project to classify crude oil conditions. As a result, all crude oil samples have their odour profile pattern extracted through the normalisation of data. The performance accuracy of the CBR classifier achieved a high rate, which is 99.31% on average. Hence, the using of E-nose and utilising CBR are excellent methods in investigating odour.